Mesons at high temperature in QCD - Gert Aarts (Nuclear Physics B - Proceedings Supplements, 2005)
We report first results for spectral functions of charmonium in 2-flavour QCD. The spectral functions are determined from vector and pseudoscalar correlators on a dynamical, anisotropic lattice. J/psi and eta_c are found to survive well into the deconfined phase before melting away at T<~2T_c. Current systematic uncertainties prevent us from drawing any definite conclusions at this stage.